2017
DOI: 10.1159/000476000
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of B-Lines on Lung Ultrasound in Volume Overload and Pulmonary Congestion: Clinical Correlations and Outcomes in Patients on Hemodialysis

Abstract: Background: Volume overload in patients on hemodialysis (HD) is an independent risk factor for cardiovascular mortality. B-lines detected on lung ultrasound (BLUS) assess extravascular lung water. This raises interest in its utility for assessing volume status and cardiovascular outcomes. Methods: End-stage renal disease patients on HD at the Island Rehab Center being older than 18 years were screened. Patients achieving their dry weight (DW) had a lung ultrasound in a supine position. Scores were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
(46 reference statements)
0
25
0
1
Order By: Relevance
“…18 Furthermore, an abnormal LUS scan (outside of COVID-19) has prognostic implications across multiple diseases. [19][20][21] Future studies are needed to determine if LUS can reliably predict clinical outcomes with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, an abnormal LUS scan (outside of COVID-19) has prognostic implications across multiple diseases. [19][20][21] Future studies are needed to determine if LUS can reliably predict clinical outcomes with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary congestion, which can remain after hemodialysis therapy, may also be correlated with a poor outcome. In a recent American study, a multivariate Cox regression analysis showed that the number of Blines at the end of hemodialysis therapy was an independent predictor of mortality [11]. Thorough removal of the water and the prevention of lung congestion at the end of hemodialysis seem to be important for a Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between pre-hemodialysis number of B-lines and mortality was already reported [6]. Another investigator reported that the number of B-lines at the end of hemodialysis therapy was related to mortality [11]. There was no report which investigates the relationship between the number of B-lines at the middle of hemodialysis therapy and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The number of B-lines is directly proportional to the degree of extravascular water accumulation. 38,39 This typically is evaluated using an 8-zone method (4 zones on each side), although a 28-zone method recently has become widespread. [40][41][42] The severity of pulmonary edema can be semiquantified by summing the amount of B-lines in the zones or by determining the number of affected zones.…”
Section: Diaphragm Dysfunctionmentioning
confidence: 99%